2020
DOI: 10.1523/jneurosci.1223-20.2020
|View full text |Cite
|
Sign up to set email alerts
|

Lysophospholipids Contribute to Oxaliplatin-Induced Acute Peripheral Pain

Abstract: Oxaliplatin, a platinum-based chemotherapeutic drug, which is used as first-line treatment for some types of colorectal carcinoma, causes peripheral neuropathic pain in patients. In addition, an acute peripheral pain syndrome develop in almost 90% of patients immediately after oxaliplatin treatment, which is poorly understood mechanistically but correlates with incidence and severity of the later-occurring neuropathy. Here we investigated the effects of acute oxaliplatin treatment in a murine model, showing th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 66 publications
(78 reference statements)
4
33
0
Order By: Relevance
“…In sterile inflammation, evoked by physical burn as well as UVB-mediated sunburn, derivates of oxidized linoleic acid increase (43,44). Lysophosphatidic acid 18:1 and lysophosphatidyl choline 16:0 and 18:1, additional metabolites deriving from phosphatidylcholine precursors, mediate neuropathic pain (45)(46)(47)(48). In a mouse model of chronic inflammation, oxidized linoleic acid-derived mediators increase in the central nervous system (49).…”
Section: Additional Oxidized Lipids Involved In Pain Perceptionmentioning
confidence: 99%
“…In sterile inflammation, evoked by physical burn as well as UVB-mediated sunburn, derivates of oxidized linoleic acid increase (43,44). Lysophosphatidic acid 18:1 and lysophosphatidyl choline 16:0 and 18:1, additional metabolites deriving from phosphatidylcholine precursors, mediate neuropathic pain (45)(46)(47)(48). In a mouse model of chronic inflammation, oxidized linoleic acid-derived mediators increase in the central nervous system (49).…”
Section: Additional Oxidized Lipids Involved In Pain Perceptionmentioning
confidence: 99%
“…Previously, we showed that oxaliplatin induced mechanical hypersensitivity 24 h after treatment [ 20 ]. For the current study, we first investigated whether the activity of the TRPM8 channel was altered in response to oxaliplatin treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Viable neurons were identified by a short KCl stimulation at the end of each measurement, causing depolarization and activation of voltage-gated calcium channels. Previously, we could observe that the mRNA expressions of TRPV1 and TRPA1 were unchanged after oxaliplatin treatment [ 20 ]. We next investigated the mRNA expression levels of several other ion channels that have previously been connected with oxaliplatin-induced hypersensitivity [ 14 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As expected, this kind of response was lower in TRPM8 knockout (KO) mice. Lysophosphatidylcholine (LPC) 18:1 and LPC 16:0, which are over-expressed in oxaliplatin-induced peripheral neuropathy, have been identified as endogenous activators of TRPV1 and TRPM8 channels, suggesting that the modulation of lipid pathways could also serve to alleviate this neuropathy [142].…”
Section: Trpm8 Agonistsmentioning
confidence: 99%